Freight Long Wagon Dynamic Analysis in S-Curve by Means of Computer Simulation - Stastniak, Pavol (Manufacturing Technology Journal, 2015)
The article deals with the dynamic analysis of long freight wagon with a low and multifunctional loading plane for intermodal transport. The main task of simulation was to verify enough overlap of buffers, when the vehicle rides through S-curve, because the wagon is equipped with non-standard construction of the front part of undercarriage. Simulation was performed in program Adams, module VI-Rail. These and similar analyzes are nowadays an integral part of the development process of rolling stock and greatly reduce the time necessary for design, tests and certification of new vehicles. In the future, it will be possible in the case of verification results replace some real tests by simulation analysis on certain conditions.
Keywords: S-curve; Long wagon; Buffers overlap; Dynamic analysis